The first mitochondrial genome of the living-fossil sawfly Macroxyela ferruginea (Hymenoptera: Xyelidae, Macroxyelinae). Issue 1 (2nd January 2020) - Zheng, Bo-Ying; Li, Ze-Kai; Li, Xiao-Fei; Zhu, Jia-Chen; Sharkey, Michael; Tang, Pu; Chen, Xue-Xin
Abstract: The living-fossil sawfly Macroxyela ferruginea (Xyelidae: Macroxyelinae) was one of the oldest species of Hymenoptera. We sequenced the mitochondrial genome, 15, 465 bp in size. All 37 typical mitochondrial genes were possessed. There is only one rearrangement of gene order, where trnM and trnQ were shuffled. We also found this order was shared with Xyela sp., which also belongs to family Xyelidae. The 13 protein-coding genes of this sequence and the other 10 species from eight superfamilies in Hymenoptera were all used for phylogenetic analysis by maximum likelihood (ML) analysis and Bayesian inference (BI), with Ascaloptynx appendiculatus from Neuroptera as an outgroup. The topology demonstrated that M. ferruginea was sister to Xyela sp., supporting that they belong to one family Xyelidae.